Sputum indoleamine-2, 3-dioxygenase activity is increased in asthmatic airways by using inhaled corticosteroids - Kittipong Maneechotesuwan (2018)
Background: Indoleamine-2, 3-dioxygenase (IDO), a tryptophan-degrading enzyme, plays a key role in the regulation of T-lymphocyte function. IDO inhibits eosinophilic inflammation in a murine asthma model, but little is known about its role in asthmatic patients or the effects of corticosteroids on this key regulatory enzyme. Objective: We studied IDO activity and the effect of inhaled corticosteroids (ICSs) in patients with asthma and how this correlated with eosinophilic inflammation. Methods: After a 1-week run-in period on no therapy, 34 asthmatic patients were treated with only short-acting β2-agonists as required or an ICS or an ICS in combination with a long-acting β2-agonist, which were required for asthma control, and the treatment was continued for a further 4 weeks. Each patient underwent sputum induction at the end of the run-in and treatment periods. Sputum supernatant specimens were analyzed for IDO activity and kynurenine concentrations by using HPLC. Results: All patients with mild intermittent and mild-to-moderate persistent asthma had low baseline IDO activity in induced sputum compared with that seen in age-matched nonasthmatic subjects. The IDO activity was markedly enhanced by either ICS (P = .03) or ICS/long-acting β2-agonist (P < .0001) treatment, and this increase negatively correlated with sputum eosinophils but was positively associated with an increase in IL-10-positive macrophages. Conclusion: ICSs might exert their anti-inflammatory activity in asthmatic airways, at least in part, through the upregulation of IDO activity associated with increased IL-10 secretion from macrophages. © 2008 American Academy of Allergy, Asthma & Immunology.